Catalogue of the family Ologamasidae Ryke (Acari: Mesostigmata) - Castilho, Raphael C.; Silva, Edmilson S.; de Moraes, Gilberto J.; Halliday, Bruce (Zootaxa, 2016)
Mites of the family Ologamasidae are very conspicuous and abundant in soil and litter, especially in the Southern Hemisphere. Little is known of their biology and behaviour, but they appear to be generalist predators. The family is placed in the Rhodacaroidea, but its status and composition have been very unstable. The existing classification and identification keys are obsolete and difficult to use. We present a historical review of the literature on the classification of the Ologamasidae, with revised diagnoses for the family and its included genera, and a new key to genera. We also present a complete catalogue of the species, with details of their nomenclature and bibliography, and a summary of the locality and habitat data for the types for each species.        The family includes a total of 467 species arranged in 44 genera. The largest genera are Gamasiphis Berlese (74 species), Gamasellus Berlese (70 species) and Geogamasus Lee (33 species). These three genera together include more than 35% of the valid species in the family. Seven of the genera are monotypic. We list a further 29 species that appear to belong to the family Ologamasidae, but which cannot be confidently assigned to a genus on the basis of the available information. We also list 74 species that have been placed in the Ologamasidae at some time, but which are now placed in other families, especially the Veigaiidae, Digamasellidae, Parasitidae, and Eviphididae.        New combinations are proposed for 15 species. The genus Pachymasiphis is described as new, because this name was not made available correctly when it was first proposed.